2007
DOI: 10.1074/jbc.m705265200
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Cleavage of Ataxin-7 by Caspase-7 Modulates Cellular Toxicity and Transcriptional Dysregulation

Abstract: Spinocerebellar ataxia type 7 (SCA7) is a polyglutamine (polyQ) disorder characterized by specific degeneration of cerebellar, brainstem, and retinal neurons. Although they share little sequence homology, proteins implicated in polyQ disorders have common properties beyond their characteristic polyQ tract. These include the production of proteolytic fragments, nuclear accumulation, and processing by caspases. Here we report that ataxin-7 is cleaved by caspase-7, and we map two putative caspase-7 cleavage sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
96
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(106 citation statements)
references
References 60 publications
10
96
0
Order By: Relevance
“…Proteolytic processing of ATXN7, believed to occur in the nucleus, has been observed in SCA7 and is thought to generate smaller more toxic polyQ fragments (Garden et al, 2002;Young et al, 2007;Yu et al, 2012;Yvert et al, 2001). We have previously shown that in the stable PC12 cell model used in this study, full-length ATXN7 is mainly found in the nucleus, whereas ATXN7 fragments localize and aggregate both in the nucleus and the cytoplasm .…”
Section: Discussionmentioning
confidence: 95%
“…Proteolytic processing of ATXN7, believed to occur in the nucleus, has been observed in SCA7 and is thought to generate smaller more toxic polyQ fragments (Garden et al, 2002;Young et al, 2007;Yu et al, 2012;Yvert et al, 2001). We have previously shown that in the stable PC12 cell model used in this study, full-length ATXN7 is mainly found in the nucleus, whereas ATXN7 fragments localize and aggregate both in the nucleus and the cytoplasm .…”
Section: Discussionmentioning
confidence: 95%
“…Proteolytic fragments containing expanded polyQ tracts are more aggregation-prone than original fulllength proteins, as has been shown for huntingtin (Cooper et al, 1998), androgen receptor , ataxin 3 (Haacke et al, 2006) and ataxin 7 (Young et al, 2007). Recently, it was also postulated that an expanded polyQ fragment was expressed in SCA8, because antisense transcription resulted in polyQ inclusions (Ikeda et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of proteolytic protein fragments harbouring a polyQ tract in aggregates (DiFiglia et al, 1997;Goti et al, 2004;Li et al, 1998;Schmidt et al, 1998) has led to the 'toxic fragment hypothesis', which states that proteolytic fragments of polyQexpanded huntingtin (Cooper et al, 1998), androgen receptor or certain ataxins (Haacke et al, 2006;Ikeda et al, 1996;Young et al, 2007) initiate protein aggregation and induce neuronal toxicity. Full-length polyQ proteins aggregate, but at a much slower rate than their proteolytic fragments .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that substrates can have a substantial preference for caspase-7 over caspase-3 or vice versa. The reported substrates with specificity for caspase-7, but not for the closely related caspase-3, are Nogo-B (SSTD2S) (38), claspin (DEYD2G) (39), and Ataxin-7 (PKMD2G and FDPD2I) (40). A substrate preference for caspase-3 over caspase-7 is found in protein phosphatase-1 inhibitor-3 (DTVD2X) (41) and in excitatory amino acid transporter EAAT2 (DTID2S) (42).…”
Section: Discussionmentioning
confidence: 99%